Advantage of Nanotechnology-Based Genome Editing System and Its Application in Crop Improvement - Ahmar, Sunny; Mahmood, Tahir; Fiaz, Sajid; Mora-Poblete, Freddy; Shafique, Muhammad Sohaib; Chattha, Muhammad Sohaib; Jung, Ki-Hung (Frontiers in Plant Science, 2021)
Agriculture is an important source of human food. However, its current practices need to be modernized and strengthened to fulfill the increasing food requirements of the growing worldwide population. Here genome editing (GE) technology has been used to produce plants with improved yields and nutritional value and higher resilience to herbicides, insects, and diseases. Many GE tools have been developed recently, including clustered regularly interspaced short palindromic repeats (CRISPR) with nucleases, a flexible and successful method. The main steps of the GE process involve providing transgenes or CRISPR to plants via specific gene delivery systems. However, these tools have certain limitations in their usage, including time-consuming and complicated protocols, potential tissue damage, DNA incorporation in the host genome, and low transformation efficiency. To overcome these issues, nanotechnology has emerged as part of a groundbreaking and modern method. The gene delivery mediated by nanoparticles is superior to conventional biomolecular approaches, enhancing the transformation efficiency for both temporal (transient) and permanent (stable) genetic modification in a wide variety of plant species. However, with the discovery of an array of advanced technologies, certain challenges in developing a short-term breeding strategy in plants remain. Thus, nanobased delivery system and plant genetic engineering challenges are discussed in detail in this paper. Here, we suggest an effective way to speed up crop improvement programs by combining current technologies, such as speed breeding and CRISPR/Cas9, with nanotechnology. The overall aim is to provide a detailed overview of nanotechnology-based CRISPR techniques for plant transformation and to suggest applications for possible crop enhancement.